2021
DOI: 10.1186/s13048-021-00891-0
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of circ-FURIN suppresses the proliferation and induces apoptosis of granular cells in polycystic ovary syndrome via miR-195-5p/BCL2 axis

Abstract: Background Polycystic ovary syndrome (PCOS) is an endocrine disease that increases the risk of infertility. Circular RNAs (circRNAs) play important roles in regulating the biological processes of PCOS. Our study was designed to explore the function of circ-FURIN in PCOS. Methods Circ-FURIN expression was detected using RT-qPCR. The protein expression of AVEN, BCL2, XIAP and AREL1 was measured using western blot. Dual-luciferase reporter and RNA pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This study is the first to identify TNFSF10 as a diagnostic marker of necroptosis in PCOS, and its specific function in the development of PCOS needs to be further investigated. BCL2 has been reported to be involved in the development of PCOS ( 56 ). Also, BCL2 was involved in necroptosis in various diseases ( 57 , 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first to identify TNFSF10 as a diagnostic marker of necroptosis in PCOS, and its specific function in the development of PCOS needs to be further investigated. BCL2 has been reported to be involved in the development of PCOS ( 56 ). Also, BCL2 was involved in necroptosis in various diseases ( 57 , 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression of BAX/BCL2 in human GCs has been shown to be higher in PCOS patients when compared to controls ( 7 , 63 ). Interestingly, BCL2 expression has been proposed to be regulated through the interaction between a circular RNA (circRNA) and a newly proposed miRNA involved in PCOS, miR-195-5p ( 63 ). However, in this current study, miR-195-5p was not identified as a differentially expressed miRNA in any of the comparisons.…”
Section: Discussionmentioning
confidence: 96%
“…We firstly identified the cytoplasmic location of circ-JA760602 in hypoxia-induced AC16 cells. circRNAs can affect cell apoptosis in various disease models by regulating the expression of apoptosis-related mRNAs (27)(28)(29). Considering the effect of circ-JA760602 on apoptosis, we detected its modulation on the expression of apoptosis-related mRNAs.…”
Section: Discussionmentioning
confidence: 99%